Advances in grinding tools and abrasives. Issue 2 (2022) - Beaucamp, Anthony; Kirsch, Benjamin; Zhu, Wule
Abstract: Because of their many applications, including automotive, aeronautics, optics, and so forth, demand for grinding tools sees unabated growth. But the energy and resource intensive nature of their manufacture leads to questions of sustainability. This paper details how recent developments in basic tool technology (structure, binder, abrasives) is increasing tool and abrasive resilience while reducing production inputs. The advent of smart grinding tools involving aspects of surface engineering, process hybridization, and process monitoring is also discussed. The paper concludes with an outlook of further energy savings, tool recycling and uses of additive manufacturing with the aim of achieving long-term sustainability.